La copie – genèse de l’image absolue dans Bouvard et Pécuchet - Judith Kasper (Flaubert: Revue Critique et Génétique)
The article has two principal concerns: first, to read Flaubert’s last novel, Bouvard et Pécuchet, as an extended reflection on the idea of a copy. Here the term copie is understood and developed in three related ways: as a mise-en-abîme structure of infinite regress; as mimetic reproduction; and as pure abundance. Second, to ask how the idea of a copy is linked to that of an image. If, in one sense, a copy may be viewed as an ideal image, as the very image of perfect reproduction, in another sense never fully developed in the second, unfinished part of the novel significantly entitled “la copie,” it is associated with a movement beyond traditional conceptions of the image and the imaginary.